Thermal Analysis of Solder Joint Based on Eddy Current Pulsed Thermography - Zhou, Xiuyun; Xue, Yun; Tian, Guiyun; Liu, Zhen (IEEE transactions on components, packaging, and manufacturing technology (2011), 2017)
Solder joint provides electronic and mechanical connections between components and substrate. Overheating and excessive temperature gradient can cause solder joint failures and then make the whole system breakdown. Thus, thermal analysis has been the hotspot in reliability evaluation of electronic packaging. This paper proposes eddy current pulsed thermography (ECPT) to investigate thermal transfer through solder joint in a surface mounted device (SMD). A 3-D electromagnetic-thermal model was built, and the ECPT system was established to analyze transient temperature distribution on the pin surface. This model introduced pseudo soldering and evaluated its impacts on thermal conduction. Thermal resistance of solder joint was calculated to characterize different pseudo soldering defects. With pseudo soldering acreage increased, thermal resistance had an approximate quadratic rise. Both simulation and experimental results indicate that the surface temperature gradually decreases with the increase of pseudo soldering acreage. This ECPT method could be applied to the thermal analysis of solder joint in SMD, and it also could provide guidance for thermal design or reliability evaluation of electronic packages.